Ameliorative potentials of Aju Mbaise extract (AME) on Dutasteride induced oxidative stress and hepatic injury in rats - Robert Ikechukwu Uroko; Elisha Uko Ogwo; Paul Nweje-Anyalowu; Ikenna Obiwuru; Chinomso Friday Aaron; Obinna Joseph Mba (Islamic Azad University, Shahrekord Branch, 2023)
Background & Aim: Aju Mbaise is a polyherbal extract with nutraceutical properties that helps to replenish the volume of blood lost during childbirth and improves breast milk secretion and the general wellbeing of the mother. This study evaluated the ameliorative potentials of Aju Mbaise extract (AME) on Dutasteride-induced oxidative stress and hepatic injury in rats. Twenty-one rats were used to assess the acute toxicity of AME. Experimental: The study for the hepatoprotective effects of AME had five groups of rats, including normal control, Dutasteride only, AME only, Dutasteride + AME (500 mg/kg) and Dutasteride+ AME (1000 mg/kg). Results: The acute toxicity result showed that AME is relatively safe for consumption. Dutasteride caused significant elevation of liver marker enzymes, including aspartate transaminase (AST), alanine transaminase (ALT), transaminase (AST), alkaline phosphatase (ALP), total bilirubin, malondialdehyde (MDA) and significantly reduced catalase, superoxide dismutase (SOD), glutathione peroxidase (GPx), reduced glutathione (GSH), total proteins, albumin, and globulin levels in the rats received only Dutasteride. In contrast, Dutasteride induced rats treated with AME showed a significant decline in the AST, ALT, ALP, MDA, and bilirubin and significantly increased SOD, GSH, GPx, total proteins, albumin, and globulin levels compared to Dutasteride induced untreated rats. The AME-treated rats showed normal liver histo-architecture, unlike the Dutasteride-induced untreated rats that showed mild to moderate vacuolar degeneration of the hepatocytes. Recommended applications/industries: The findings show that AME ameliorates Dutasteride caused rats oxidative stress and hepatic injury.